Cardiac Gene Expression Methods and Protocols - Zhang, Jun.; Rokosh, Gregg; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Cardiac Gene Expression: Methods and Protocols presents both cutting-edge and established methods for studying cardiac gene expression. The protocols provide a template for solid research, and cover the process through screening, analysis, characterization, and functional confirmation of novel genes or known genes with a new function. Section I, Cardiac Gene Expression Profiling: The Global Perspective, discusses several different approaches to examining, identifying, and analyzing changes in transcriptome gene expression. Section II, Cardiac Gene Regulation: Gene-Specific mRNA Measurement in the Myocardium, outlines more sensitive and gene-targeted expression methods. Section III, Cardiac Gene Regulation: Promoter Characterization in the Myocardium, provides protocols for the study of underlying gene regulation mechanisms by focusing on the interaction of transcription factors with their cognate cis binding elements. Section IV, In Silico Assessment of Regulatory cis-Elements and Gene Regulation, and Section V, Cardiac Single Network Polymorphisms, emphasize new analytical approaches for deciphering the functional elements buried in the 3 billion nucleotides of the human genome and other model genomes. The concluding section, Gene Overexpression and Targeting in the Myocardium, highlights methods that facilitate overexpression or cardiac-specific targeted gene deletion.
Cardiac Gene Expression -- Microarray Analysis of Gene Expression in Murine Cardiac Graft Infiltrating Cells -- Expression Profiling Using Affymetrix GeneChip® Probe Arrays -- Serial Analysis of Gene Expression (SAGE) -- Functional Genomics by cDNA Subtractive Hybridization -- Statistical Methods in Cardiac Gene Expression Profiling -- Cardiac Gene Regulation -- Measurement of Cardiac Gene Expression by Reverse Transcription Polymerase Chain Reaction (RT-PCR) -- Quantitative (Real-Time) RT-PCR in Cardiovascular Research -- RNase Protection Assay for Quantifying Gene Expression Levels -- In Situ Hybridization -- Cardiac Gene Regulation -- Characterization of cis-Regulatory Elements and Transcription Factor Binding -- Mapping Transcriptional Start Sites and In Silico DNA Footprinting -- Characterization of Cardiac Gene Promoter Activity -- In Silico Assessment of Regulatory cis-Elements and Gene Regulation -- Comparative Genomics -- Developing Computational Resources in Cardiac Gene Expression -- Cardiac Single Nucleotide Polymorphisms -- In Silico Analysis of SNPs and Other High-Throughput Data -- Discovery and Identification of Sequence Polymorphisms and Mutations with MALDI-TOF MS -- Gene Overexpression and Targeting in the Myocardium -- Conditional Targeting -- Cardiomyocyte Preparation, Culture, and Gene Transfer -- Adeno-Associated Viral Vector-Delivered Hypoxia-Inducible Gene Expression in Ischemic Hearts -- Lentivirus-Mediated Gene Expression.
Keywords: Life sciences; Human genetics; Cardiology; Biochemistry; Bioinformatics; Life Sciences; Biochemistry, general; Human Genetics; Cardiology; Bioinformatics; Electronic books